Teknologi Budidaya Maggot untuk Kelompok Pembudidaya Ikan “Panle Bersaudara”, Desa Danda Jaya, Barito Kuala - Noor Arida Fauzana; Pahmi Ansyari; Slamet Budianto; Ahmad Faisal Azhar (Jurnal Surya Masyarakat, 2024)
Community Service with the Community Partnership Program (PKM) scheme was carried out for the "Panle Brothers" Fish Cultivator Group (Pokdakan), Danda Jaya Village, Rantau Badauh District, Barito Kuala Regency. Pokdakan cultivates catfish and catfish, with a cultivated fish pond area of only 0.2 ha, and the size of the fish pond plots varying from 25 – 100 m2. Productivity is low, because Pokdakan is still very dependent on commercial feed which is very expensive with a small profit margin. Businesses for making independent feed have begun to be carried out using local ingredients, but the use of animal ingredients still relies on fish meal. The solution to overcome this problem is to carry out the dissemination of maggot cultivation technology from Black Soldier Fly (BSF) flies. This is the right and strategic step to substitute fish meal, because the protein contained in maggots is equivalent to or even more than fish meal. Research results state that maggots contain between 40-60% protein so that using maggots in feed formulations, even if given directly fresh to carnivorous fish such as catfish and catfish, can save production costs of up to 40%. Dissemination of this technology is delivered using theoretical explanations, demonstrations, training and intensive assistance during activities. The results obtained showed that the group of cultivators were very enthusiastic in accepting the technology presented, there was an increase in knowledge of 328.57% and an increase in skills of 541.67% regarding maggot cultivation. The supporting factor for this activity is that the Pokdakan group shows great interest and motivation in this technology. The inhibiting factor is that very hot weather causes maggot growth to be less than optimal.